D-dimer, BNP/NT-pro-BNP, and creatinine are reliable decision-making biomarkers in life-sustaining therapies withholding and withdrawing during COVID-19 outbreak - Smadja, David M.; Fellous, Benjamin A.; Bonnet, Guillaume; Hauw-Berlemont, Caroline; Sutter, Willy; Beauvais, Agathe; Fauvel, Charles; Philippe, Aurélien; Weizman, Orianne; Mika, Delphine; Juvin, Philippe; Waldmann, Victor; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The decision for withholding and withdrawing of life-sustaining treatments (LSTs) in COVID-19 patients is currently based on a collegial and mainly clinical assessment. In the context of a global pandemic and overwhelmed health system, the question of LST decision support for COVID-19 patients using prognostic biomarkers arises. Methods In a multicenter study in 24 French hospitals, 2878 COVID-19 patients hospitalized in medical departments from 26 February to 20 April 2020 were included. In a propensity-matched population, we compared the clinical, biological, and management characteristics and survival of patients with and without LST decision using Student's t-test, the chi-square test, and the Cox model, respectively. Results An LST was decided for 591 COVID-19 patients (20.5%). These 591 patients with LST decision were secondarily matched (1:1) based on age, sex, body mass index, and cancer history with 591 COVID-19 patients with no LST decision. The patients with LST decision had significantly more cardiovascular diseases, such as high blood pressure (72.9 vs. 66.7%, p = 0.02), stroke (19.3 vs. 11.1%, p < 0.001), renal failure (30.4 vs. 17.4%, p < 0.001), and heart disease (22.5 vs. 14.9%, p < 0.001). Upon admission, LST patients were more severely attested by a qSOFA score ≥2 (66.5 vs. 58.8%, p = 0.03). Biologically, LST patients had significantly higher values of D-dimer, markers of heart failure (BNP and NT-pro-BNP), and renal damage (creatinine) (p < 0.001). Their evolutions were more often unfavorable (in-hospital mortality) than patients with no LST decision (41.5 vs. 10.3%, p < 0.001). By combining the three biomarkers (D-dimer, BNP and/or NT-proBNP, and creatinine), the proportion of LST increased significantly with the number of abnormally high biomarkers (24, 41.3, 48.3, and 60%, respectively, for none, one, two, and three high values of biomarkers, trend p < 0.01). Conclusion The concomitant increase in D-dimer, BNP/NT-proBNP, and creatinine during the admission of a COVID-19 patient could represent a reliable and helpful tool for LST decision. Circulating biomarker might potentially provide additional information for LST decision in COVID-19.